Design of Dominantly Proportional PID Controller Using a Single Commercially Available Active Component - Sagbas, Mehmet; Koksal, Muhammet; Ayten, Umut Engin (IEEE, 2013)
A proportional integral derivative (PID) controller employing only a single commercially available active component, two resistors and two capacitors is presented. The PID controller circuit has low impedance voltage output which can be easily cascaded with other voltage-mode (VM) structures. The effects caused by the non-ideality of the current feedback operational amplifier (CFOA) are analyzed. The performance of the proposed circuit is demonstrated by using PSPICE simulations.
Keywords: Current conveyors; Current feedback operational amplifiers; PID controllers; AD844; INVERSE FILTERS; REALIZATION; NULLORS; CCII; CFOA; Engineering; Telecommunications